From Awareness to Action: Pioneering Solutions for Women’s UTI Challenges in the Era of Precision Medicine - Haley E; Luke N (Dove Medical Press, 2024)
Emery Haley, Natalie Luke Department of Clinical Research, Pathnostics, Irvine, CA, USACorrespondence: Natalie Luke, Pathnostics, 15545 Sand Canyon Suite 100, Irvine, CA, 92618, USA, Tel +1-714-966-1221, Fax +1-714-966-1231, Email nluke@pathnostics.comAbstract: This article aims to bring clinicians' awareness to the widespread impact of urinary tract infection (UTI) on the lives of women and to the advances that offer hope for future improvements in the diagnosis and management of UTI. Thanks to physiological, anatomical, and lifestyle factor differences, women face heightened vulnerability to UTIs compared to men. In fact, women are four times more likely than men to develop a UTI and around half of these women encounter UTI recurrence, which is a significant source of both physical and psychosocial burdens. Despite the current shortcomings in diagnosis and management, emerging diagnostic technologies promise to identify UTIs more accurately and rapidly, offering women hope for a revolution in UTI management. Meanwhile, clinicians have the opportunity to reduce the psychosocial burden by recognizing the value of patients' lived experiences and ensuring their care plan is in alignment with their patients' goals and expectations for medical care.Keywords: women's health, urinary tract infection, urine culture, multiplex-polymerase chain reaction, metagenomic next-generation sequencing, mass spectrometry